Circulating microRNAs as biomarkers for ischemic heart disease: a systematic review and gene set enrichment analysis - Alcibahy, Yasmine; Darwish, Radwan; Abu-Sharia, Ghena; Maes, Quinten; Elgamassy, Omar (Frontiers in Medicine, 2025)
IntroductionIschemic heart disease (IHD) remains a major global health burden, highlighting the urgent need for early, non-invasive diagnostic biomarkers. MicroRNAs (miRNAs), small non-coding RNA molecules that regulate gene expression, have emerged as promising candidates due to their stability in circulation and involvement in cardiovascular processes. This systematic review aimed to evaluate the potential of specific miRNAs as early diagnostic biomarkers in IHD.MethodsWe conducted a systematic review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Searches were performed in PubMed, Scopus, and Web of Science databases up to June 31, 2024. Eligible studies were selected based on predefined inclusion criteria. We identified recurrently dysregulated miRNAs and used miRTarBase to retrieve experimentally validated gene targets. Subsequently, gene set enrichment analysis (GSEA) was performed using Enrichr, referencing BioPlanet, KEGG, and Panther pathway libraries. Functional annotation was further explored using TAM 2.0.ResultsA total of 38 studies met the inclusion criteria. Among the reported miRNAs, miR-126, miR-21, miR-145, miR-92a, and miR-155 were the most frequently and consistently dysregulated across various IHD subtypes. Although expression patterns varied, these miRNAs were recurrently implicated in IHD-related processes. GSEA revealed enrichment of their gene targets in key pathways such as p53, TGF-β, and FoxO signaling, as well as in processes involving apoptosis and angiogenesis critical in vascular injury, remodeling, and immune activation. Several cancer-related pathways were also enriched, underscoring molecular overlaps between tumorigenesis and atherosclerosis. TAM 2.0 functional annotation supported these findings, linking the selected miRNAs to smooth muscle differentiation, cytokine signaling, and regulation by key transcription factors including SMAD4, STAT3, and AP-1.DiscussionOur findings suggest that a panel combining the identified miRNAs may offer greater diagnostic value for IHD than individual markers, given their involvement in multiple IHD-related biological processes and pathways. The recurrent dysregulation of these miRNAs across diverse studies supports their potential as components of a robust, non-invasive diagnostic tool. However, expression variability and pathway overlap with other diseases, such as cancer, indicate the need for further validation. Larger prospective studies are warranted to validate their clinical applicability in IHD screening and risk stratification.Systematic review registrationInternational Prospective Register of Systematic Reviews (PROSPERO), identifier CRD42024583265.